2020
DOI: 10.1536/ihj.19-395
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the Impact of Pre-Procedural Serum Albumin on Mortality in Patients Undergoing Transcatheter Aortic Valve Replacement

Abstract: Pre-procedural serum albumin's impact on prognosis after transcatheter aortic valve replacement (TAVR) has been studied. Literature on the prognostic role of serum albumin in the survival of patients undergoing TAVR shows conflicting results. This meta-analysis was conducted to evaluate the impact of pre-procedural serum albumin on outcomes after TAVR. A comprehensive literature search of EMBASE, MEDLINE, and the Cochrane Library was undertaken through July 2019. The primary end points were 30-day and one-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…In our study, we found that a reduced albumin level (below the median of 4.0 g/dL) is an independent risk factor for all‐cause mortality. This is consistent with previous studies that have shown that hypoalbuminaemia is associated with an increased risk of mortality after TAVR 37,38 …”
Section: Discussionsupporting
confidence: 94%
“…In our study, we found that a reduced albumin level (below the median of 4.0 g/dL) is an independent risk factor for all‐cause mortality. This is consistent with previous studies that have shown that hypoalbuminaemia is associated with an increased risk of mortality after TAVR 37,38 …”
Section: Discussionsupporting
confidence: 94%
“…Moreover, sarcopenic patients presented higher levels of C‐reactive protein (CRP) and Erythrocyte Sedimentation Rate (ESR) 27 . In TAVR patients, both poor nutritional status, 28 low albumin 29 and subclinical inflammation 30 have been associated to increased all‐cause mortality rates at follow‐up. Moreover, TAVR recipients deemed sarcopenic at baseline according to low skeletal muscle index (SMI), present not only longer hospital stay but also worse 1‐year health related quality of life (HR‐QOL) 31 …”
Section: Discussionmentioning
confidence: 99%
“… 23 Our data also showed that hypoalbuminemia was associated with increased mortality in TAVR patients, likely a marker for frailty. 24 In our cohort, NYHA Class at the time of TAVR was not an independent risk factor for mortality on the basis of the multivariable Cox analysis. These risk factors for mortality may help inform preprocedural risk assessment and clinical management.…”
Section: Discussionmentioning
confidence: 58%